ST-MVL: Filling Missing Values in Geo-sensory Time Series Data - Yi, Xiuwen; Zheng, Yu; Zhang, Junbo; Li, Tianrui (Proceedings of the 25th International Joint Conference on Artificial Intelligence, 2016)
Many sensors have been deployed in the physical world, generating massive geo-tagged time series data. In reality, we usually lose readings of sensors at some unexpected moments because of sensor or communication errors. Those missing readings do not only affect real-time monitoring but also compromise the performance of further data analysis. In this paper, we propose a spatio-temporal multi-view-based learning (ST-MVL) method to collectively fill missing readings in a collection of geo-sensory time series data, considering 1) the temporal correlation between readings at different timestamps in the same series and 2) the spatial correlation between different time series. Our method combines empirical statistic models, consisting of Inverse Distance Weighting and Simple Exponential Smoothing, with data-driven algorithms, comprised of User-based and Item-based Collaborative Filtering. The former models handle the general missing cases based on empirical assumptions derived from history data over a long period, standing for two global views from a spatial and temporal perspective respectively. The latter algorithms deal with special cases where empirical assumptions may not hold, based on recent contexts of data, denoting two local views from a spatial and temporal perspective respectively. The predictions of the four views are aggregated to a final value in a multi-view learning algorithm. We evaluate our method based on Beijing air quality and meteorological data, finding our model’s advantages beyond ten baseline approaches. The data and codes have been released!